Congenital goitrous hypothyroidism: mutation analysis in the thyroid peroxidase gene - Belforte, Fiorella Sabrina (2012)
Background: Iodide organification defect (IOD) is characterized by a reduced ability of the thyroid gland to retain iodide resulting in hypothyroidism. Mutations in thyroid peroxidase (TPO) gene appear to be the most common cause of IOD and are commonly inherited in an autosomal recessive fashion. The TPO gene is located on the chromosome 2p25. It comprises 17 exons, covers approximately 150 kb of genomic DNA and codes 933 amino acids. Objetives: In this study, we characterize the clinical and molecular basis of seven patients from four unrelated families with congenital hypothyroidism (CH) because of IOD. Design and Methods: All patients underwent clinical, biochemical and imaging evaluation. The promoter and the complete coding regions of the human TPO along with the flanking intronic regions were analysed by single-strand conformation polymorphism analysis and direct DNA sequencing. Segregation analysis of mutations was carried out, and the effect of the novel missense identified mutations was investigated by 'in silico' studies. Results: All subjects had congenital and persistent primary hypothyroidism. Three novel mutations: c.796C>T [p.Q266X], c.1784G>A [p.R595K] and c.2000G>A [p.G667D] and a previously reported mutation: c.1186-1187insGGCC [p.R396fsX472] have been identified. Four patients were compound heterozygous for p.R396fsX472/p.R595K mutations, two patients were homozygous for p.R595K, and the remaining patient was a compound heterozygous for p.Q266X/p.G667D. Conclusions: Our findings confirm the genetic heterogeneity of TPO defects and the importance of the implementation of molecular studies to determinate the aetiology of the CH with dyshormonogenesis.